2007
DOI: 10.1007/s10346-007-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative basin characterisation to refine debris-flow triggering criteria and processes: an example from the Italian Western Alps

Abstract: This paper investigates rapid channelized debris flow related to rainfalls in small alpine basins. Its goal is to evaluate and correlate different geological and technical aspects with predisposing and triggering factors that can control these phenomena. The study area is the upper part of the Susa Valley where 12 small basins were selected. For each of them, lithological, geomorphological, climatic and technical information were mapped and analysed. Debris-flow triggering conditions, flow and depositional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 9 publications
3
39
0
2
Order By: Relevance
“…The morphological characteristics are summarized in Table 1. It can therefore be concluded that most debris flows will also originate at slope angles close to 30 • , and this observation is supported at other sites [26]. Field surveys revealed that landslide and debris flow in the Umyeonsan region were the result of three main steps: (1) initial failure produces a shallow landslide trace caused by the transitional sliding of the loose colluvium overlying gneiss bedrock (Figure 3a).…”
Section: Geological and Geomorphological Datasupporting
confidence: 53%
See 1 more Smart Citation
“…The morphological characteristics are summarized in Table 1. It can therefore be concluded that most debris flows will also originate at slope angles close to 30 • , and this observation is supported at other sites [26]. Field surveys revealed that landslide and debris flow in the Umyeonsan region were the result of three main steps: (1) initial failure produces a shallow landslide trace caused by the transitional sliding of the loose colluvium overlying gneiss bedrock (Figure 3a).…”
Section: Geological and Geomorphological Datasupporting
confidence: 53%
“…It can be deduced that the summer season receives a large portion of the annual rainfall [32]. Figure 6 shows the hourly and cumulative rainfall for [26][27] July 2011 recorded at the rain gauges installed at Seocho and Namhyun stations. The cumulative 24-h rainfall ending at 12:40 p.m. on 27 July 2011 was 364.5 mm and 425.5 mm, respectively (i.e., very heavy rainfall).…”
Section: Rainfall Characteristicsmentioning
confidence: 99%
“…The deposit of the debris flow shows a different horizontal gradation along the fan with clast-rich lobes, levee-like boulder train and distal sand-rich lobes that are characteristic of this type of catchment lithology group (Tiranti et al, 2008). Boulders could be found on the alluvial fan apex, while sand and silt in the more distal part.…”
Section: Debris-flow Event and Surveysmentioning
confidence: 96%
“…The assessment of rainfall threshold values for debris flow initiation are based in most cases on statistical empirical approaches using large data sets without detailed knowledge of the different triggering processes and its influencing factors [2,29].…”
Section: Discussionmentioning
confidence: 99%